SISTEM INFORMASI PENJUALAN MENU MAKANAN PADA RESTORAN DI KATA SENJA KOPI BERBASIS WEB - Gllen yusuf abbel; Ilman Zuhri Yadi; Yesi Novaria Kunang (P3M Institut Teknologi Pagar Alam, 2023)
The aim of this study is to create a web-based information platform for placing food orders at the establishment named Twilight Coffee. The approach adopted for constructing this platform follows the stages of extreme programming in software development, encompassing Design, Coding, and Testing. The system's design phase employs a standardized modeling language (UML), incorporating use case diagrams, activity diagrams, and sequence diagrams. Implementing a food ordering system streamlines the food selection procedure. By introducing a web-based menu ordering system accessible via Android mobile devices, this initiative represents an enhancement to the current facilities and infrastructure. This enhancement is aimed at elevating employee efficiency in catering to customer needs